2002
DOI: 10.1590/s0104-66322002000200014
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of acetoin production by Hanseniaspora guilliermondii using experimental design

Abstract: -The synthesis of acetoin in YM medium and under aerobic conditions by Hanseniaspora guilliermondii was studied. Experimental design and surface response analysis were employed to evaluate the influence of glucose concentration, temperature and pH on the process. The experiments were carried out in shaking flasks under controlled temperature. Five different levels of initial concentration of glucose, temperature and pH were used with variations from 17 to 81 g/L, from 24 to 36 o C and from 4.0 to 6.0, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…To assess the significance of each individual factor on the acetoin production, the results of Plackett-Burman design were analyzed by the analysis of variance (ANOVA). [25] The results are given in Table 3. The analysis of variance showed that yeast extract, corn steep liquor, and urea had significant influences on the response as Optimizing Fermentation Medium 537 evidenced by their p values (<0.1, significant at 10% level).…”
Section: The Plackett-burman Designmentioning
confidence: 99%
“…To assess the significance of each individual factor on the acetoin production, the results of Plackett-Burman design were analyzed by the analysis of variance (ANOVA). [25] The results are given in Table 3. The analysis of variance showed that yeast extract, corn steep liquor, and urea had significant influences on the response as Optimizing Fermentation Medium 537 evidenced by their p values (<0.1, significant at 10% level).…”
Section: The Plackett-burman Designmentioning
confidence: 99%
“…The production of acetoin by microbial fermentation has been reported to gain increasing interest due to its safety and environmental friendliness [3,4]. Intensive efforts have been taken to enhance microbial production of acetoin, including screening of high-yield acetoin-producing strains [5,6], metabolic engineering breeding [7][8][9], and fermentation optimization [9][10][11]. The price of chemically generated acetoin (racemic) is over $ 16.2/kg, and biologically generated dietary acetoin can be two times more expensive [12].…”
Section: Introductionmentioning
confidence: 99%
“…A high-yielding strain is pivotal for the commercial fermentation of AC. Many microorganisms could produce AC, including Saccharomyces carlsbergensis [3], Saccharomyces cerevisiae [4], Hanseniaspora guilliermondii [5], Lactococcus lactis [6], Leuconostoc citrovorum [7], and Zygosaccharomyces bailii [8], etc. In particular, Serratia marcescens H13 (75.2 g/L) [9], Bacillus licheniformis MEL 09 (41.2 g/L) [10], and Bacillus pumilus DSM 16187 (63.0 g/L, EP 2005081882) exhibited high AC-producing ability from glucose.…”
Section: Introductionmentioning
confidence: 99%